Recent progresses in novel in vitro models of primary neurons: A biomaterial perspective - Zhang, Jiangang; Yang, Huiyu; Wu, Jiaming; Zhang, Dingyue; Wang, Yu; Zhai, Jiliang (Frontiers in Bioengineering and Biotechnology, 2022)
Central nervous system (CNS) diseases have been a growing threat to the health of mankind, emphasizing the urgent need of exploring the pathogenesis and therapeutic approaches of various CNS diseases. Primary neurons are directly obtained from animals or humans, which have wide application including diseases modeling, mechanism exploration and drug development. However, traditional two dimensional (2D) monoculture cannot resemble the native microenvironment of CNS. With the increasing understanding of the complexity of CNS and the remarkable development of novel biomaterials, in vitro models have experienced a great innovation from 2D monoculture towards three dimensional (3D) multicellular culture. The scope of this review includes the progresses of various in vitro models of primary neurons in recent years to provide a holistic view of the modalities as well as applications of primary neuron models and how they have been connected with the revolution of biofabrication techniques. A special attention has been paid to the interaction between primary neurons and biomaterials. First, a brief introduction about the history of CNS modeling and primary neuron culture was conducted. Next, detailed progresses in novel in vitro models were discussed ranging from co-culture, ex vivo model, spheroid, scaffold-based model, 3D bioprinting model and microfluidic chip. Modalities, applications, advantages and limitations of the aforementioned models were described separately. Finally, we look forward to the future prospects, providing new insights into how basic science research methodologies has advanced our understanding of the CNS, and highlight some future directions of primary neuron culture in the next few decades.